Planktonic Organisms as Bio-indicators of Pollution in Aquatic Environments - K U Sheethal; T.S. Annappaswamy; M.T. Lakshmipathi; Khalasi Binal Rajeshbhai; Aitwar Vaijnath Sambayya (International Journal of Marine Life, 2024)
Planktonic organisms play a pivotal role in aquatic ecosystems, serving as vital bio indicators of pollution levels. This review offers a thorough exploration of their significance in assessing environmental health in aquatic environments. We delve into the diverse array of planktonic taxa, encompassing phytoplankton, zooplankton, and bacterioplankton, and examine their responses to various pollutants such as nutrient enrichment, chemical contaminants, and microplastics. These organisms exhibit remarkable sensitivity to environmental changes, underscoring their utility in monitoring pollution impacts. By adopting interdisciplinary perspectives, we evaluate the efficacy of planktonic bioindicators in gauging ecosystem health and guiding management strategies. Understanding their reactions to pollutants not only enhances our ability to detect and quantify pollution levels but also provides insights into the broader ecological repercussions on planktonic communities and aquatic ecosystems at large. The review discusses methodological approaches for plankton sampling, data analysis, and interpretation in pollution assessment programs, emphasizing the critical need for standardized protocols and advanced analytical techniques. By synthesizing existing knowledge and pinpointing research gaps, this review aims to deepen our comprehension of how pollution affects planktonic communities. Integration of planktonic bioindicators into holistic approaches for aquatic ecosystem management and conservation is imperative for sustainable environmental stewardship. Future research directions should prioritize refining monitoring techniques, addressing emerging pollutants, assessing the cumulative impacts of multiple stressors on planktonic organisms, and fostering international collaboration to establish global standards for effective environmental monitoring and management strategies. This synthesis underscores the pivotal role of planktonic organisms in bolstering our capacity to safeguard and manage aquatic resources effectively amidst ongoing environmental challenges.
Keywords: Mercury; Methylmercury; Pollution; ecosystem; pesticides